Transforming into a Cashless World: Factors Driving Brand Loyalty of Touch ‘N Go E-Wallet in Malaysia - Hui Shan Lee; Lavanessh A/P Rajandran; Yung Wei Lai; Kirubasshini A/P DM Karunamurthy; Vivek Anand; B. Shashank; Rehan Faisal Qadri (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2022)
In this digital era world, people can buy anything via mobile wallets instead of physical cash. A transformation of a cashless society becomes a new consumer behavior in this 21st century. Especially during the COVID-19 pandemic, people are more encouraged to use an e-Wallet to lower the virus's risk. Therefore, Touch ‘n Go with millions of users, has become an important application in this cashless world. This paper aims to examine the factors driving brand loyalty to Touch ‘n Go e-wallet. There are 150 Touch ‘n Go users who participated in our survey and the results were analyzed using SPSS. With that, we found out that perceived usefulness, perceived ease of use, reliability, and safety affect brand loyalty. This research provides insightful results and information about Touch ‘n go e-Wallet. Keywords: Brand Loyalty, Perceived Ease of Use, Perceived Usefulness, Reliability and Safety, Touch ‘n Go